Perceived Neighborhood Environmental Factors That Maximize the Effectiveness of a Multilevel Intervention Promoting Physical Activity Among Latinas. Issue 2 (February 2018) - Perez, Lilian G.; Kerr, J.; Sallis, J. F.; Slymen, D.; McKenzie, T. L.; Elder, J. P.; Arredondo, E. M.
Purpose: This study tested whether a multilevel physical activity (PA) intervention had differential effects on PA according to participants' perceptions of their neighborhood environment. Design: Two-group cluster randomized controlled trial. Setting: San Diego, California. Subjects: Analytical sample included 319 Latinas (18-65 years) from churches randomized to the following conditions: PA (n = 8 churches, n = 157 participants) or attention control (n = 8 churches, n = 162 participants). Intervention: Over 12 months, PA participants were offered free PA classes (6/wk), while attention control participants were offered cancer prevention workshops. Measures: Baseline and 12-month follow-up measures included self-report and accelerometer-based moderate to vigorous physical activity (MVPA), sociodemographics, and perceived neighborhood environment variables. Analysis: Mixed-effects models examined each PA outcome at 12-month follow-up, adjusted for church clustering, baseline PA, and sociodemographics. We tested interactions between 7 baseline perceived environment variables and study condition. Results: Neighborhood esthetics was the only significant moderator of intervention effects on accelerometer-based MVPA and self-report leisure-time MVPA. Participants in the PA intervention had significantly higher PA at follow-up than attention control participants, only when participants evaluated their neighborhood esthetics favorably. Conclusion: Perceived neighborhood esthetics appeared to maximize the effectiveness of a multilevel PA intervention among Latinas. For sustainable PA behavior change, the environments in which Latinas are encouraged to be active may need to be evaluated prior to implementing an intervention to ensure they support active lifestyles.